Metodología y análisis de la Encuesta Nacional de Salud y Nutrición Continua 2020-2024. - Romero-Martínez, Martín; Shamah-Levy, Teresa; Barrientos-Gutiérrez, Tonatiuh; Cuevas-Nasu, Lucia; Bautista-Arredondo, Sergio; Colchero, M. Arantxa; Gaona-Pineda, Elsa B.; Martínez-Barnetche, Jesús; Alpuche-Aranda, Celia; Gómez-Acosta, Luz M.; Mendoza-Alvarado, Laura R.; Rivera-Dommarco, Juan; et al. (Salud Pública de México)
Objective. To describe the methodology and analysis procedures of the National Health and Nutrition Survey 2024 (Ensanut Continua 2024). Materials and methods. Ensanut Continua 2024 is the fifth survey in the Ensanut Continua 2020-2024 series. Ensanut Continua 2024 will enable inferences about the health and nutrition status of the population in Mexico in 2024; moreover, it will complete the state sample sizes to allow inferences about the inhabitants of the 32 states during the period 2021-2024. In this document are the main elements of Ensanut Continua 2024 are described: sampling procedures, estimation, measurement, and logistical organization. Results. Ensanut Continua 2024 is expected to have the following complete questionnaires: 10 640 household, 12 085 adult, 3 589 adolescent, 2 424 school-aged children, and 2 346 preschool-aged children. Additionally, it is anticipated that at least 1 000 complete household interviews will be conducted per state during the period 2021-2024. Conclusions. Ensanut Continua 2020-2024 will provide national, state, and trend estimates for the period 2020-2024; furthermore, Ensanut Continua 2020-2024 can serve as the basis for making annual state-level estimates in the subsequent years.